Development of 6–12 GHz evanescent–mode two–pole low–loss tunable bandpass filter. Issue 10 (October 2015) - Cho, Young Seek; Joshi, Himanshu; Liu, Xiaoguang; Sigmarsson, Hjalti H.; Chappell, William J.; Peroulis, Dimitrios
ABSTRACT A very low‐loss tunable evanescent‐mode cavity bandpass filter (BPF) with one‐octave (6–12 GHz) tuning range is presented. To implement a very low‐insertion loss with wideband operation, a new coaxial‐feed structure is devised in the tunable BPF. Across the entire tuning range, the achieved insertion loss is less than 0.5 dB. The 3‐dB fractional bandwidth varies from 6.1% at 6 GHz to 12% at 12 GHz. The tenability is realized using silicon microelectromechanical systems diaphragms with slits that are electrostatically actuated. Direct comparison between a solid diaphragm and the proposed stress‐reduced diaphragm with slits is presented. The bulk of the filter is realized using physical machining of a tall printed circuit board. This article shows the upper frequency limit that is feasible using milling. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2418–2422, 2015